Metal-ceramic partial fixed dentures: a retrospective study - Fernanda Ferruzzi LIMA; Fabíola Pontes AZEVEDO; Bárbara Margarido BRONDINO; Rodrigo Moreira Bringel DA COSTA; Brunna Mota FERRAIRO; Vinícius Cappo BIANCO; Vinícius Carvalho PORTO; José Henrique RUBO (Faculdade São Leopoldo Mandic, 2020)
ABSTRACT Objective Metal-ceramic prosthesis are the treatment of choice in oral rehabilitation because of their high survival rates. However, there are few reports in the scientific literature about factors that lead to fractures of metal-ceramic prostheses. The aim of this study was to evaluate whether prostheses units number, abutment type and number, type of the prostheses, prostheses position in the mouth, bruxism and occlusal plaque influence the incidence of fractures in fixed metal-ceramic prostheses. Methods For this study, 16 patients were selected, totaling 74 metal-ceramic prostheses installed between 2000-2010, with follow up of at least four years. Besides dental history, other information was collected, such as patients' gender and age, prostheses installation date, and the ceramic system used. In case of prostheses fracture, a questionnaire was applied to identify signs of bruxism. A clinical evaluation was done to evaluate the prostheses integrity and opposing dentition characteristics. Success, failure and survival rates were determined. Results The results showed that the success rate of metal-ceramic prostheses was 87.8% and the survival rate was 89.1%. In addition, the success rate was independent of patient age, prostheses installation time, number of prosthesis, number of prosthesis' units and abutments. The qualitative variables also did not show significant statistical results between success and failure rates. Conclusion It was concluded that metal-ceramic prostheses have high success and survival rates, what guarantees longevity and indication of this type of prostheses in daily practice.